Rapid Power Compensation-Based VSC-HVDC Control Strategy for Low-Frequency Oscillation Suppression of the Island Power System - Lv, Haipeng; Abuduwayiti, Xiwang; Meng, Lingpeng; Shi, Cunjin (Frontiers in Energy Research, 2021)
Owing to the increased proportion of new energy power generation , such as wind power and photovoltaic, connected to the island grid, the system powered by the voltage source converter (VSC) based HVDC (VSC-HVDC) is prone to oscillate or even lose stability when disrupted. In this paper, considering the rapid power compensation (RPC), an active power control strategy has been suggested for the receiving-end converter station of VSC-HVDC that could efficiently suppress the low-frequency oscillation of the island power system. Firstly, the mechanism of VSC-HVDC inhibiting low-frequency oscillation of island grid is analyzed in this paper and then it theoretically determines that the damping capacity and inertia level of RPC control strategy are stronger than conventional droop control and inertia control. Secondly, the receiving-end converter station switches from RPC mode to droop control, in order to allow the system to have a smooth recovery from the steady-state operation in the later stage of oscillation suppression. Moreover, detailed control logic and state switching strategies have been designed. Finally, the simulation reflects that the proposed control strategy has a stronger oscillation suppression ability, allowing it to obtain rapid suppression of low-frequency oscillation.